New institutional economics and the environment: Conceptual foundations and policy implications - Jouni Paavola; William Neil Adger (University of East Anglia, The Centre for Social and Economic Research on the Global Environment (CSERGE), 2002)
This paper reviews literature in and around new institutional economics to assess its contributions to, and limitations in, research on environmental decision-making and governance. The paper also proposes ways to increase the fruitfulness of new institutional approach for environmental research. The paper identifies the conceptualisation of environmental problems as instances of interdependence and the acknowledgement of positive transaction costs as the hallmarks of new institutional approach to the environment. The paper also discusses how the new institutional approach can be extended so as to acknowledge plural motivations and limited cognitive capacity. The paper investigates how evolutionary and collective action theories frame the choice and change of environmental governance institutions and discusses how the notion of social capital can enrich institutional analyses. The paper concludes that the new institutional approach to the environment is particularly attractive for under-standing institutional or policy design and policy implementation.
Keywords: 330; environment and development; environmental governance; institutions; New institutional economics; Social Capital; Neue Institutionenökonomik; Umweltökonomik; Umweltpolitik; Theorie